The effect of relational priming on young children's interpretation of noun-noun compounds - Douglas, Michelle S. (The University of Edinburgh, 2010)
Abstract: When interpreting noun-noun combinations, such as dog scarf, one must distinguish a plausible relationship between the two nouns. Usually there are several relations that could reasonably be used, resulting in the intended meaning of the noun-noun compound being ambiguous. Based upon Raffray, Pickering and Branigan’s (2007) conclusion that adults are reliably more likely to interpret a new concept by applying a noun-noun relationship that they have encountered a short time before, the current study set out to investigate whether this finding can be applied to pre-school children. A picture-expression matching task was used to test nursery aged children’s susceptibility to relational priming (mean age 3;11). The study draws together two main conclusions. Firstly, children show significant relational priming that mirrors adult behaviour on the same task. Secondly, children showed a significantly higher priming effect in cases where the head noun was repeated than when the modifier was repeated. These outcomes are discussed with relevance to children’s broad use of noun-noun compounds, their application of the whole object constraint theory when constructing a meaning for a novel concept and the tendency for them to substantiate stronger links between trials when the head noun is repeated. The study also posits that when selecting an appropriate interpretation children use aspects of both relation- and schema- based theories in their approach.
Keywords: Relational priming; noun-noun compounds; children